Sistema informático para el registro, monitoreo y análisis estadísticos de las condiciones del caudal del río San Pablo, La Maná. - Palacios Pinargote, Patricio Hernan (2020)
This project was carried out in the research area of the Technical University of Cotopaxi Extension La Maná and aims to implement a web system for monitoring, recording and statistical analysis of the conditions of the flow of the San Pablo river, Canton La Maná, Cotopaxi Province. This system shows in real time the conditions in which the level of the river's flow is, which will help reduce material losses and safeguard the lives of the inhabitants of the riverbank due to flooding, which in previous years has happened. This system will have an alarm that will be active by means of a Raspberry Pi that will be activated when the river flow level exceeds the normal range of water flow. As a contribution to the community of La Maná canton, this project was developed with the implementation of a web system which will give a report on the flow levels for a certain time, all these data will be reflected in a web application, which counts with a type of user; The administrator is responsible for making changes to the application. The tools that were used for software development were, a Raspberry Pi board, like a computer, with the Java language, the MySQL database manager, such as Frame-work CodeIgniter with bootstrap which had preference according to the researches -ion that was made, are the most appropriate for development and do not require to acquire a license, with the exception of the sublime text editor text 3. However, it should be noted that the methodology chosen for this research project is the SCRUM which can be adapted to any type of project and adopts an incremental development skill, instead of the complete planning and execution of the system.